At the edge of individual cognitive-behavioural policies: how to walk the public health path to effectively improve population health? - Baltica Cabieses (Instituto Nacional de Salud Pública, 2013)
Most countries worldwide have recognised the significance of contextual social determinants of health (SDH) on population health. This essay challenges current public health views focused on individual risk-factors and motivates an  evidenceinformed debate in this matter. I argue that despite both international consensus and a growing body of evidence to support the relevance of addressing such more distant SDH through public policies, most governments remain focused on the modification of individual health-risk behaviours like smoking, excessive alcohol consumption, heavily fatted diets and lack of physical exercise. Decades after following this same policy path, many countries have not achieved the expected reduction in rates of health-risk behaviours, and some have even experienced an increase in these risky behaviours over time. Policies addressing contextual SDH might take longer to implement, but could be more effective in the long-run, as structural modifications promote more sustainable changes to a larger proportion of the population.